High-Dose Melatonin and Ethanol Excipient Combined with Therapeutic Hypothermia in a Newborn Piglet Asphyxia Model - Robertson, Nicola J. (Sci Rep, 2020)
With the current practice of therapeutic hypothermia for neonatal encephalopathy, disability rates and the severity spectrum of cerebral palsy are reduced. Nevertheless, safe and effective adjunct therapies are needed to optimize outcomes. This study’s objective was to assess if 18 mg/kg melatonin given rapidly over 2 h at 1 h after hypoxia-ischemia with cooling from 1–13 h was safe, achieved therapeutic levels within 3 h and augmented hypothermic neuroprotection. Following hypoxia-ischemia, 20 newborn piglets were randomized to: (i) Cooling 1–13 h (HT; n = 6); (ii) HT+ 2.5% ethanol vehicle (HT+V; n = 7); (iii) HT + Melatonin (HT+M; n = 7). Intensive care was maintained for 48 h; aEEG was acquired throughout, brain MRS acquired at 24 and 48 h and cell death (TUNEL) evaluated at 48 h. There were no differences for insult severity. Core temperature was higher in HT group for first hour after HI. Comparing HT+M to HT, aEEG scores recovered more quickly by 19 h (p < 0.05); comparing HT+V to HT, aEEG recovered from 31 h (p < 0.05). Brain phosphocreatine/inorganic phosphate and NTP/exchangeable phosphate were higher at 48 h in HT+M versus HT (p = 0.036, p = 0.049 respectively). Including both 24 h and 48 h measurements, the rise in Lactate/N-acetyl aspartate was reduced in white (p = 0.030) and grey matter (p = 0.038) after HI. Reduced overall TUNEL positive cells were observed in HT+M (47.1 cells/mm(2)) compared to HT (123.8 cells/mm(2)) (p = 0.0003) and HT+V (97.5 cells/mm(2)) compared to HT (p = 0.012). Localized protection was seen in white matter for HT+M versus HT (p = 0.036) and internal capsule for HT+M compared to HT (p = 0.001) and HT+V versus HT (p = 0.006). Therapeutic melatonin levels (15–30mg/l) were achieved at 2 h and were neuroprotective following HI, but ethanol vehicle was partially protective.